2000
DOI: 10.1046/j.1365-2125.2000.00167.x
|View full text |Cite
|
Sign up to set email alerts
|

Paracetamol, alcohol and the liver

Abstract: It is claimed that chronic alcoholics are at increased risk of paracetamol (acetaminophen) hepatotoxicity not only following overdosage but also with its therapeutic use. Increased susceptibility is supposed to be due to induction of liver microsomal enzymes by ethanol with increased formation of the toxic metabolite of paracetamol. However, the clinical evidence in support of these claims is anecdotal and the same liver damage after overdosage occurs in patients who are not chronic alcoholics. Many alcoholic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
110
1
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(118 citation statements)
references
References 130 publications
5
110
1
2
Order By: Relevance
“…Because the subjects with ALF reporting use of Յ4 g acetaminophen per day were often alcohol abusers (65%) and the amount of daily alcohol consumed was greater than that reported by patients who admitted to taking Ͼ4 g acetaminophen per day (data not shown), ethanol may still serve as an important co-factor in these lower-dose subjects. 4,6,13,24,[34][35][36] The overall transplant-free survival rate of 65% in acetaminophen subjects is comparable to that of prior studies and continues to be more favorable than that observed for most other ALF causes. 13,37,38,39 The use of the King's criteria at admission to predict outcome was inaccurate, and use of the APACHE II provided a more accurate of assessment outcome.…”
Section: Discussionsupporting
confidence: 70%
“…Because the subjects with ALF reporting use of Յ4 g acetaminophen per day were often alcohol abusers (65%) and the amount of daily alcohol consumed was greater than that reported by patients who admitted to taking Ͼ4 g acetaminophen per day (data not shown), ethanol may still serve as an important co-factor in these lower-dose subjects. 4,6,13,24,[34][35][36] The overall transplant-free survival rate of 65% in acetaminophen subjects is comparable to that of prior studies and continues to be more favorable than that observed for most other ALF causes. 13,37,38,39 The use of the King's criteria at admission to predict outcome was inaccurate, and use of the APACHE II provided a more accurate of assessment outcome.…”
Section: Discussionsupporting
confidence: 70%
“…A third explanation is that staggered overdoses act as a surrogate marker for other risk factors for adverse outcomes following paracetamol overdose, such as older age and chronic alcohol abuse [22,24], both of which were more common in the staggered overdose group. Whilst acute alcohol consumption has an inhibitory effect on the oxidative metabolism of paracetamol and may be hepatoprotective [25], this protective effect is probably lost in the context of chronic alcohol abuse or where there is a delay between alcohol and paracetamol intake [26], perhaps explaining why staggered overdose patients had worse clinical outcomes despite the increased incidence of acute alcohol consumption at the time of overdose (54% vs. 39%) in this subgroup.…”
Section: Figurementioning
confidence: 97%
“…16,[20][21][22] However, there is some uncertainty about the significance of chronic ethanol consumption as an independent risk factor, because the association is confounded by delayed presentation to hospital and initiation of NAC. [23][24][25][26] Exclusion of patients who presented more than 24 hours after ingestion does not allow us to address whether chronic ethanol excess might influence the development of hepatotoxicity in patients who present late. Induction of cytochrome 2E1 requires chronic exposure to ethanol concentrations >250 mg ⁄ dL, which might be encountered only in patients with extremely heavy drinking patterns.…”
Section: Discussionmentioning
confidence: 99%